Mukimi's “Sayohatnoma” (Travelogue) Work: Problem of Text History - Abdulkhakimovich , Jabborov Nurboy (International Journal of Psychosocial Rehabilitation, 2020)
This article was devoted to the study of the history of the text of the work "Sayohatnoma" by Muhammad Aminkhoja Mukimi, a well-known representative of Uzbek literature of the national revival period. In analyzing the work, it was based on the texts of the inventory digital manuscripts 7521, 1325, 5666, 6352 of "Sayohatnoma" kept in the fund of the Institute of Oriental Studies of the Academy of Sciences of Uzbekistan. When it was necessary, the text of the work was compared with copies in current editions. It was found that the total volume of the "Sayohatnoma", each of the sections which consist of four lines, is actually 77 section - 308 lines, and based on existing publications, only 244 lines of the text of the work became known to the scientific community. Also, a scientific assessment was given to the circumstances such as the text of the "Sayohatnoma" was "ideologically edited" under the requirements of communist ideology, as a result of which, firstly, the essence of the existing idea in the play was blurred, and secondly, ideas that were not in the play were included in the text. The authors examined the textual history of Mukimi's "Sayohatnoa" based on the following factors: a) factors influencing the writing of the work, the process of emergence of creative goals and plans; b) the history of the book in manuscript sources; c) the issue of the text of the work in current editions; d) the relationship of scientific interpretations of the work with the history of the text. The process of emergence of the poet's creative intention was analyzed. It was proved through scientific analysis that interpretations made without relying on authenticity have no scientific basis. In the study of the text history of the "Sayohatnoma", scientific conclusions were drawn about the need to rely on the texts of the work in manuscript sources.